Soviet nuclear nechnoscience: topography of the field and new avenues of research - Guth, Stefan; Gestwa, Klaus; Penter, Tanja; Richers, Julia (Cahiers du monde russe, 2019)
In 1904, Frederick Soddy, who would later receive the Nobel Prize for his seminal studies in radiochemistry, speculated that the “new alchemists” who had unlocked the awe‑inspiring power of the atom would “turn wastelands green, melt the polar ice caps, and transform the planet into a friendly Garden of Eden.” But he also predicted that the state to possess the first viable atomic weapon would achieve world domination. The significance of nuclear technology, at once promising and terrible, sh...
Gesehen am 02.02.2021